Heart failure a companion to Braunwald's heart disease - Mann, Douglas L. (Philadelphia Saunders, 2011)
Dr. Douglas L. Mann, one of the foremost experts in the field, presents the 2nd Edition. This completely reworked edition covers the scientific and clinical guidance you need to effectively manage your patients and captures the dramatic advances made in the field over the last five years. Now in full color, this edition features eleven new chapters, including advanced cardiac imaging techniques, use of biomarkers, cell-based therapies and tissue engineering, device therapies, and much more. Stay current with the latest developments concerning cardiac imaging, use of biomarkers in patient evaluation, device therapy, heart failure in special populations, disease prevention, preserved ejection fraction, cell-based therapy and tissue engineering, managing heart failure with malignancy, cognitive impairment, and much more. Stay abreast of the most dynamic and fastest-moving areas in cardiology with the latest information.
Section 1. Basic Mechanisms of Heart Failure -- Section 2. Mechanisms of Disease Progression in Heart Failure -- Section 3. Etiological Basis for Heart Failure -- Section 4. Clinical Assessment of Heart Failure -- Section 5. Therapy for Heart Failure.
Companion v. to: Braunwald's heart disease / edited by Peter Libby [and others]. 8th ed. c2008.
Includes bibliographical references and index.
Keywords: Heart failure; Heart Failure